2017
DOI: 10.1590/s1518-8787.2017051000090
|View full text |Cite
|
Sign up to set email alerts
|

Noncommunicable diseases and the use of health services: analysis of the National Health Survey in Brazil

Abstract: OBJECTIVE To assess whether sex, education level, and health insurance affect the use of health services among the adult Brazilian population with chronic noncommunicable diseases (NCD).METHODS Data from a cross-sectional survey were analyzed, the National Health Survey (PNS). Frequency of use of services in the population that referred at least one NCD were compared with the frequency from a population that did not report NCD, according to sex, education level, health insurance, and NCD number (1, 2, 3, 4, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
116
0
84

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(238 citation statements)
references
References 17 publications
12
116
0
84
Order By: Relevance
“…Also, NCD have a long duration and evolve slowly, disproportionately affecting lowand middle-income countries, the poorest and most vulnerable populations 3,5 . Recent data from the National Health Survey (NHS) in Brazil indicated that people with higher schooling and health insurance have more access to health services and medical appointments 6,7 . They also have a lower prevalence of risk factors 8 and are less affected by disabilities caused by NCD, which illustrates the inequalities in health 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, NCD have a long duration and evolve slowly, disproportionately affecting lowand middle-income countries, the poorest and most vulnerable populations 3,5 . Recent data from the National Health Survey (NHS) in Brazil indicated that people with higher schooling and health insurance have more access to health services and medical appointments 6,7 . They also have a lower prevalence of risk factors 8 and are less affected by disabilities caused by NCD, which illustrates the inequalities in health 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Usually, men use health services less often compared with women [37,38], and they may also ignore or delay healthcare due to illness [38]. Contrarily, women tend to use health services more frequently, mostly for routine screening, and prevention [39,40]. A previous study investigated different professional activities and demonstrated that work-related injuries are more prevalent in male workers, and although women presented a higher incidence of sickness absence, the difference was small (less than 4%) [26].…”
Section: Discussionmentioning
confidence: 99%
“…A presença de comorbidades foi indicada como fator a ser considerado. Estudo brasileiro associou a presença de doença crônica não transmissível com o aumento de internação 23 .…”
Section: Discussionunclassified